Index investing : a low cost, low risk strategy to investment success - Kumar, Abhishek (New Delhi Sage, 2020)
"Most investors get it wrong when it comes to understanding the nuances of the equity market. It is not that they are ignorant or lack the requisite skills to understand the factors affecting the equity market, but mainly because they learn misleading information from the market players and financial intermediaries. Consecutively, these entities thrive and flourish while the investor is left to stare at the market in dismay, wondering where all the money has gone"--
Keywords: Index mutual funds; Investments